A method for regulating the distribution of precipitates in a Cu-Ni-Si alloy
Patent Information
- Application Number
- CN202611137200.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的在于克服现有Cu-Ni-Si合金制备技术中因室温预变形引入的位错分布不均匀,导致后续δ-Ni2Si析出相分布不均匀,进而造成合金强度、塑性与导电率难以同步优化的技术缺陷,提供一种调控Cu-Ni-Si合金析出相分布的方法
(1)传统室温变形过程中,位错的交滑移和攀移易于发生,导致位错迅速重排为不均匀的胞状结构,胞壁处位错密集而胞内稀疏。本发明采用液氮温区(-196℃)的深冷预变形,从物理本质上改变了这一过程。深冷环境显著降低了原子扩散速率和位错攀移能力,强烈抑制了变形过程中的动态回复。这使得位错难以通过交滑移和攀移进行重排,被迫以平面滑移阵列的形式均匀分布于基体中,同时,深冷变形诱导产生高密度层错和纳米孪晶。最终,本发明在合金基体中构建了由平面滑移位错阵列、层错和纳米孪晶界组成的晶体缺陷网络,这些缺陷中位错呈平面阵列分布,纳米孪晶界和层错在空间上分布均匀,而非室温变形的局部聚集状态。这一均匀、高密度的缺陷网络,正是后续实现均匀析出的物理基础。
Smart Images

Figure CN122979791A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of copper alloy material preparation and processing technology, specifically a method for controlling the distribution of precipitated phases in Cu-Ni-Si alloys. Background Technology
[0002] Cu-Ni-Si alloys are a typical type of precipitation-strengthened copper alloy. Due to their high strength, high conductivity, and good wear resistance, they are widely used in electrical components with high overall performance requirements, such as electronic lead frames, connectors, and relays. The final performance of these alloys, especially the balance between strength and conductivity, mainly depends on the size, number density, and uniformity of the δ-Ni₂Si nanophase precipitated from the supersaturated solid solution during the aging process.
[0003] Currently, the typical thermomechanical treatment route for preparing Cu-Ni-Si alloys in industry is "solution treatment + cold deformation + aging treatment". Its core principle is: first, a supersaturated solid solution is obtained through solution treatment; then, crystal defects such as dislocations are introduced into the alloy matrix using cold deformation; finally, during aging, these defects act as heterogeneous nucleation sites, promoting the precipitation of δ-Ni2Si phases from the matrix, thereby achieving precipitation strengthening. In this classic process route, the dislocation density and distribution introduced by cold deformation (usually room temperature rolling) play a decisive role in the subsequent precipitation behavior.
[0004] However, traditional room temperature cold deformation processes have significant technical limitations. During room temperature deformation, dislocations are prone to cross-slip and climb, forming a typical dislocation cellular structure. This cellular structure is characterized by dislocations unevenly accumulating at the cell walls, while the intracellular dislocation density is relatively low. This uneven dislocation distribution directly leads to uneven precipitation behavior during subsequent aging: δ-Ni₂Si precipitates preferentially nucleate and grow extensively at the dislocation cell walls, while nucleation sites are scarce in the intracellular region, resulting in a sparse distribution of precipitates. This localized precipitation difference ultimately leads to a microstructure with uneven hardness at the alloy scale. Under external force, the sparsely precipitated soft regions are prone to preferential deformation, while the precipitated hard regions restrict deformation coordination. This deformation incoordination not only easily leads to localized stress concentration, limiting the improvement of alloy plasticity, but also, due to the varying degrees of solute atoms (Ni, Si) remaining in the matrix, adversely affects further optimization of conductivity.
[0005] To address these issues, researchers have made several attempts in recent years. One approach is to simply increase the room-temperature cold rolling deformation to introduce a higher density of dislocations and increase nucleation sites. However, the dynamic recovery effect is significant at high dislocation densities, with newly generated dislocations annihilating or rearranging with existing dislocations, limiting the effective utilization of nucleation sites. Another approach is to add microalloying elements (such as Mg, Zn, and Cr) to regulate precipitation behavior or refine grains. However, adding additional alloying elements not only increases material costs and process complexity but may also introduce unnecessary second phases or negatively impact conductivity.
[0006] In summary, the key technical challenge to further improve the overall performance of Cu-Ni-Si alloys is to obtain high-density, uniformly distributed nucleation sites through optimized thermomechanical treatment processes without altering the basic alloy composition, thereby controlling the distribution of δ-Ni2Si precipitates. Summary of the Invention
[0007] The purpose of this invention is to overcome the technical defects in existing Cu-Ni-Si alloy preparation techniques, where uneven dislocation distribution introduced by room temperature pre-deformation leads to uneven distribution of subsequent δ-Ni2Si precipitates, making it difficult to simultaneously optimize alloy strength, plasticity, and conductivity. This invention provides a method for controlling the distribution of precipitates in Cu-Ni-Si alloys. This method aims to introduce uniform, high-density crystal defects into the alloy matrix through a specific cryogenic pre-deformation process. These defects serve as heterogeneous nucleation sites for δ-Ni2Si precipitates, thereby achieving precise control over the size and distribution of the precipitates, ultimately obtaining Cu-Ni-Si alloys with superior overall performance.
[0008] To achieve the above-mentioned objective, this invention provides a method for controlling the distribution of precipitated phases in Cu-Ni-Si alloys, characterized by comprising the following steps: Step (1): Using the solution-treated Cu-Ni-Si alloy as raw material, the raw material is subjected to cryogenic pre-deformation treatment. The cryogenic pre-deformation is carried out in the liquid nitrogen temperature range, with a total deformation of 65% to 85%, completed in 5 to 8 passes. After each pass of rolling, the alloy is immersed in liquid nitrogen and held for 10 to 30 minutes. Cryogenic pre-deformation can introduce crystal defects into the raw material. The crystal defects include planar slip dislocation arrays, stacking faults, and nanotwins. Step (2): The Cu-Ni-Si alloy after cryogenic pre-deformation is subjected to aging treatment at a temperature of 400-450°C and a holding time of 2-4 hours, so that the δ-Ni2Si precipitate can nucleate and grow using the crystal defects as heterogeneous nucleation points, thereby controlling the distribution of the δ-Ni2Si precipitate in the Cu-Ni-Si alloy.
[0009] Preferably, the cryogenic pre-deformation is cryogenic rolling.
[0010] Preferably, in the Cu-Ni-Si alloy obtained in step (2), the number density of the δ-Ni2Si precipitate phase is 74.63 μm. -2 .
[0011] Preferably, in the Cu-Ni-Si alloy obtained in step (2), the proportion of δ-Ni2Si precipitates with a size of less than 20 nm is 39.22%, the proportion of δ-Ni2Si precipitates with a size of 20-30 nm is 53.59%, and the proportion of δ-Ni2Si precipitates with a size of 30-40 nm is 7.19%.
[0012] Preferably, the δ-Ni2Si precipitates are spherical or ellipsoidal and distributed in the alloy matrix and at the crystal defects.
[0013] Preferably, steps (1) and (2) are repeated once, which can improve the number density of the δ-Ni2Si precipitate phase.
[0014] Preferably, the Cu-Ni-Si alloy obtained in step (2) has a conductivity of 48.70% IACS, a tensile strength of 716.42 MPa, and an elongation of 12.71%.
[0015] Beneficial effects: (1) In traditional room temperature deformation, cross-slip and climb of dislocations are prone to occur, leading to rapid rearrangement of dislocations into a non-uniform cellular structure with dense dislocations at the cell wall and sparse dislocations inside the cell. This invention employs cryogenic pre-deformation in the liquid nitrogen temperature range (-196℃), fundamentally altering this process. The cryogenic environment significantly reduces the atomic diffusion rate and dislocation climb capability, strongly suppressing dynamic recovery during deformation. This makes it difficult for dislocations to rearrange through cross-slip and climb, forcing them to be uniformly distributed in the matrix in the form of a planar slip array. Simultaneously, cryogenic deformation induces the generation of high-density stacking faults and nanotwins. Ultimately, this invention constructs a crystal defect network in the alloy matrix composed of a planar slip dislocation array, stacking faults, and nanotwin boundaries. In these defects, dislocations are distributed in a planar array, and nanotwin boundaries and stacking faults are spatially uniformly distributed, rather than the localized aggregation state of room temperature deformation. This uniform, high-density defect network is the physical basis for subsequent uniform precipitation.
[0016] (2) According to the classical heterogeneous nucleation theory, the nucleation rate is proportional to the effective nucleation site density, and the nucleation energy barrier is related to the interface energy and the local strain field. Although the dislocation cell walls introduced by room temperature deformation can serve as nucleation sites, their uneven distribution leads to local enrichment of precipitates at the cell walls, while the intracellular nucleation sites are scarce, resulting in sparse precipitation and severe spatial unevenness. The uniformly distributed high-density crystal defects introduced in this invention, especially stacking faults and nanotwin boundaries, far exceed the number introduced by room temperature deformation, providing more heterogeneous nucleation sites for δ-Ni2Si. During aging, δ-Ni2Si nucleates and grows at the alloy matrix and crystal defects. Quantitative characterization confirms that the precipitate number density of the alloy obtained in this invention is as high as 74.63 μm. -2 The traditional room temperature process only produces 14.21 μm. -2 The yield is increased by approximately 5.25 times. Simultaneously, due to the spatially uniform distribution of nucleation sites, the precipitated phase also achieves a uniform distribution, fundamentally avoiding the problem of local enrichment in traditional processes. EDS surface scan analysis clearly shows that after treatment by the method of this invention, Ni elements are uniformly distributed in the matrix without obvious local segregation, while in the comparative example, Ni elements are significantly enriched in regions such as dislocation cell walls, further confirming the significant improvement in the uniformity of precipitated phase distribution from a chemical composition perspective.
[0017] (3) In the precipitates obtained by the present invention, the proportion of precipitates with a size less than 20 nm is 39.22%, the proportion of precipitates with a size of 20–30 nm is 53.59%, and the proportion of precipitates with a size of 30–40 nm is 7.19%. The precipitates are spherical or ellipsoidal and uniformly distributed near the matrix and crystal defects. In contrast, in the traditional room temperature process, the proportion of precipitates with a size of 20 nm–50 nm is approximately 68.11%. As can be seen from the comparison, the average size of the δ-Ni2Si precipitates obtained by the method of the present invention is slightly reduced from the average ECD of 22.15 nm to 21.76 nm compared with the traditional room temperature process, and the average Feret size is reduced from 30.11 nm to 28.92 nm, while the number density and area fraction of precipitates are increased to 74.63 μm. -2And 2.40%. This precipitation characteristic of "slightly reduced average size and significantly increased number density and area fraction" precisely reflects the essential advantages of the method of this invention in terms of precipitation thermodynamics and kinetics: the high-density uniform defects introduced by cryogenic pre-deformation provide sufficient heterogeneous nucleation sites, allowing δ-Ni2Si to fully nucleate and grow to a limited extent during aging. Due to the large number and uniform distribution of nucleation sites, and the limited total amount of solute atoms available per unit volume, the precipitation reaction proceeds more fully and competitively, prompting more Ni and Si solute atoms to precipitate from the copper matrix in the form of more and finer δ-Ni2Si phase particles, thus resulting in a lower concentration of solute atoms remaining in the matrix. The direct physical consequence of this precipitation characteristic is a significant reduction in the degree of lattice distortion of the copper matrix. Lattice distortion caused by solute atoms is one of the main sources of conduction electron scattering in copper alloys. The less residual solute, the smaller the lattice distortion, and the weaker the scattering effect on conduction electrons. Experimental data confirms that the alloy obtained by this invention achieves a conductivity of 48.70% IACS, which is approximately 2.5% higher than the 47.52% IACS achieved by traditional room temperature processes. Simultaneously, it boasts a high conductivity of 74.63 μm. -2 The high number density of precipitates in this invention results in a significantly greater number of strengthening particles than in traditional processes, effectively hindering dislocation movement. The tensile strength of the alloy reaches 716.42 MPa, an increase of approximately 4.0% compared to the 689.09 MPa of the traditional process. Therefore, this invention creatively achieves a unique combination of precipitation characteristics: a slight reduction in precipitate size and a substantial increase in number density. Essentially, the high-density, uniform nucleation sites induced by cryogenic pre-deformation promote the full occurrence of the precipitation reaction during aging, and the extremely high density of nucleation sites inhibits excessive growth of the precipitate. The direct effect of this feature is that a significant reduction in matrix lattice distortion (beneficial to conductivity) and the effective introduction of high-density strengthening particles (beneficial to strength) are achieved simultaneously, breaking the traditional understanding of the inverse relationship between strength and conductivity.
[0018] (4) Another key performance improvement brought about by the uniform distribution of precipitates is reflected in plasticity. In traditional processes, the local enrichment of precipitates at the dislocation cell walls leads to significant strength differences between micro-regions. During plastic deformation, the sparsely precipitated soft regions deform preferentially, while the precipitated hard regions restrict deformation. This uneven deformation inevitably leads to local stress concentration and premature fracture. The present invention achieves a uniform distribution of precipitates in the matrix, making the strength of different regions in the alloy tend to be consistent. Under load, it can undergo uniform and coordinated plastic deformation through dislocation slip. Therefore, the elongation of the alloy obtained by the present invention reaches 12.71%, which is about 68.8% higher than the 7.53% of the traditional process, and the matching of strength and plasticity is significantly improved.
[0019] (5) Analyzing the variation of conductivity with aging time further reveals the advantages of this invention in precipitation kinetics. As the aging time increases from 2 hours to 4 hours, the conductivity of the products obtained by both the method of this invention and the conventional process gradually increases, and the conductivity of the method of this invention is always higher than that of the conventional process. When the aging time is extended to the range of 4-5 hours, the conductivity of the product obtained by the method of this invention shows a gradual decreasing trend, while the conductivity of the conventional room temperature process continues to increase slowly, but its conductivity value at 5 hours is still lower than the peak value of 48.70% IACS reached by the method of this invention at 4 hours. This variation has important physical implications: the method of this invention, due to sufficient nucleation sites and low nucleation energy barrier, completes most of the precipitation reaction and reaches the peak conductivity within a relatively short aging time (3-4 hours). In contrast, the conventional process, due to limited and unevenly distributed nucleation sites, proceeds with a slower precipitation reaction, and its conductivity can still slowly increase at 4-5 hours, but its kinetic lag means that its peak value can never surpass that of the method of this invention. This pattern, from the perspective of macroscopic performance changes, demonstrates the significant advantages of this invention in promoting uniformity and full analysis.
[0020] In summary, this invention achieves successful control over the size and distribution of the δ-Ni2Si precipitates through cryogenic pre-deformation, simultaneously improving the strength (716.42 MPa), plasticity (12.71%), and conductivity (48.70% IACS) of the Cu-Ni-Si alloy. This provides an effective and well-mechanism-clear solution to the long-standing technical challenge of coordinating comprehensive performance. Attached Figure Description
[0021] Figure 1 TEM images of crystal defects (dislocation arrays, stacking faults, nanotwins) introduced by the cryogenic pre-deformation of this invention.
[0022] Figure 2 This is a TEM image showing the distribution of δ-Ni2Si precipitates along twin boundaries and dislocation walls after aging treatment according to the present invention.
[0023] Figure 3 This is a histogram comparing the precipitate size distribution of the present invention with that of the traditional room temperature pre-deformation process.
[0024] Figure 4 The image shows a comparison of the Ni element EDS surface scan distribution of the present invention and the traditional room temperature pre-deformation process, where (a) is the Ni element distribution of the precipitated phase regulated by the cryogenic pre-deformation of the present invention, and (b) is the Ni element distribution of the precipitated phase of the traditional room temperature pre-deformation process.
[0025] Figure 5 This is a comparison of the conductivity of the present invention and the traditional room temperature pre-deformation process over aging time. Detailed Implementation
[0026] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.
[0027] This invention provides a method for controlling the distribution of precipitated phases in Cu-Ni-Si alloys. The invention uses a solution-treated Cu-Ni-Si alloy (e.g., C70250 alloy) as the starting material. The purpose of solution treatment is to fully dissolve the alloying elements (Ni, Si) into the copper matrix, forming a supersaturated solid solution, thus preparing for subsequent aging precipitation.
[0028] The core process of this invention includes the following two main steps: Step (1), Cryogenic Pre-deformation: The solution-treated Cu-Ni-Si alloy is cryogenically pre-deformed in the liquid nitrogen temperature range (-196℃), with cryogenic rolling being the preferred deformation method. The process parameters for this step are controlled as follows: the total deformation is controlled between 65% and 85%. The total deformation is one of the key parameters for regulating the crystal defect density. A larger deformation provides sufficient driving force for the induction of dislocation multiplication, stacking fault formation, and nanotwins, ensuring that a sufficient density of crystal defects can be introduced. If the deformation is too low, the defect density will be insufficient, and the nucleation sites will be limited; if the deformation is too high, it may lead to edge cracking of the alloy or increase the difficulty of subsequent processing. The total deformation is completed in 5 to 8 passes. After each rolling pass, the alloy sample needs to be quickly immersed in liquid nitrogen and held for 10 to 30 minutes. The use of multiple passes combined with inter-pass liquid nitrogen insulation serves two purposes: firstly, it ensures that the sample recovers to liquid nitrogen temperature before each pass, guaranteeing the entire deformation process is conducted in a cryogenic environment; secondly, the cryogenic environment effectively suppresses dynamic recovery during deformation, maximizing the preservation of crystal defects such as dislocations and stacking faults. The holding time after each pass must be sufficient to ensure uniform temperature throughout the sample, preventing uneven deformation microstructure caused by temperature inhomogeneity. Through this cryogenic pre-deformation treatment, high-density, uniformly distributed crystal defects can be introduced into the Cu-Ni-Si alloy raw material. These defects mainly include planar slip dislocation arrays (such as geometrically necessary dislocations and statistically stored dislocations), stacking faults, and nanotwins (Σ3 twin boundaries). These defect types and their distribution patterns form the material basis for subsequent control of precipitate distribution in this invention. Step (2), Aging Treatment: The Cu-Ni-Si alloy after cryogenic pre-deformation is subjected to isothermal aging treatment. The process parameters for this step are as follows: aging temperature is 400-450℃, and holding time is 2-4 hours. Within this temperature and time range, the supersaturated Ni and Si atoms in the alloy matrix have sufficient diffusion capacity, and the driving force is moderate, so that the crystal defects (such as dislocations, stacking faults, and nanotwin boundaries) introduced in step (1) can be used as heterogeneous nucleation sites to preferentially nucleate and grow into δ-Ni2Si precipitates. The core function of this step is that the high-density, uniformly distributed crystal defects introduced by cryogenic pre-deformation, especially stacking faults and nanotwin boundaries, provide a large number of uniformly distributed heterogeneous nucleation sites. During the aging process, the δ-Ni2Si precipitates form nuclei at these sites in a uniform and high-density manner. Their size is limited by the diffusion field of the surrounding solute atoms and the spacing between nucleation sites, thus avoiding the local enrichment or coarsening of the precipitates caused by uneven distribution of nucleation sites (dislocation cell structure) in traditional processes. Ultimately, this achieves precise control over the size and distribution of the δ-Ni2Si precipitates in the alloy.
[0029] As a further preferred embodiment of the present invention, steps (1) and (2) can be repeated once, i.e., a two-stage processing process of "deep cryogenic pre-deformation + aging + deep cryogenic pre-deformation + aging" can be adopted. Repeated processing can reintroduce defects and promote further precipitation, which can further improve the number density of δ-Ni2Si precipitates.
[0030] Example 1
[0031] This embodiment provides a method for controlling the morphology and distribution of precipitated phases in C70250 Cu-Ni-Si alloy sheet and strip through cryogenic pre-deformation. The specific steps are as follows: (1) Cryogenic pre-deformation: The C70250 alloy strip after solution treatment is cryogenically rolled in the liquid nitrogen temperature zone (-196℃) with a total deformation of 75%, divided into 5 passes. After each pass, the sample is immersed in liquid nitrogen for 30 minutes to ensure that the sample temperature drops uniformly to the liquid nitrogen temperature, so as to fully introduce high-density planar slip dislocation array, stacking faults and nanotwins; (2) Aging treatment: The alloy after cryogenic pre-deformation is subjected to isothermal aging treatment at 420℃ for 3 hours.
[0032] Example 2
[0033] This embodiment provides a method for controlling C70250 Cu-Ni-Si alloy strip. The steps are basically the same as those in Embodiment 1. The only difference is that, in order to obtain a higher precipitate density, after step (2) of Embodiment 1, the deep cryogenic pre-deformation and aging treatment are repeated once each (i.e., secondary deep cryogenic rolling + secondary aging).
[0034] Comparative Example 1 This comparative example provides a method for treating C70250 Cu-Ni-Si alloy using a conventional room temperature pre-deformation process. The steps include: cold rolling the solution-treated C70250 alloy sheet and strip at room temperature with a total deformation of 75%, divided into 5 passes, with no special heat preservation treatment between passes; and then performing isothermal aging treatment at 420℃ for 3 hours.
[0035] Performance testing methods The microstructure and various properties of the alloys obtained in Example 1 and Comparative Example 1 were tested, and the specific test methods are as follows: For microstructure characterization, transmission electron microscopy (TEM) was used to observe crystal defects and morphology and distribution of precipitates in the alloy; energy dispersive spectroscopy (EDS) was used to perform elemental surface scanning to analyze the uniformity of Ni and Si element distribution.
[0036] Regarding the number density and size statistics of precipitated phases, the number of precipitated phase particles per unit area (number density) was counted using TEM bright-field images or high-resolution images and image analysis software. The size of no less than 200 precipitated phase particles was also counted, and the proportion of each size range was calculated.
[0037] For mechanical property testing, a uniaxial tensile test was conducted at room temperature in accordance with GB / T 228.1 standard to determine the tensile strength and elongation after fracture of the alloy.
[0038] For conductivity testing, the conductivity of the alloy was determined using the double bridge method or an eddy current conductivity meter, and the results were expressed as the International Standard for Annealed Copper (%IACS).
[0039] Test Results and Analysis (1) Analysis of microstructure characteristics First, TEM observation was performed on the alloy of Example 1 after cryogenic pre-deformation treatment. For example... Figure 1 As shown, a high-density array of planar slip dislocations, numerous stacking faults, and nanotwins formed in the alloy matrix. These crystal defects exhibit a planar array distribution of dislocations, while the nanotwin boundaries and stacking faults are spatially uniformly distributed, promoting the uniform nucleation of precipitates along these defects, rather than the localized aggregation commonly seen in room temperature rolling. This microstructure clearly demonstrates that the cryogenic environment effectively suppressed dynamic recovery during deformation, preventing dislocations from rearranging into cellular structures through cross-slip and climb, forcing them to remain in a planar array form and successfully inducing the formation of stacking faults and nanotwins. These uniform, high-density crystal defects provide spatially uniform heterogeneous nucleation sites for the δ-Ni₂Si precipitates during subsequent aging.
[0040] The alloy from Example 1, after aging treatment, was then observed using TEM. Figure 2 As shown, a large number of spherical or ellipsoidal δ-Ni2Si precipitates are distributed along crystal defects. This distribution characteristic directly proves that δ-Ni2Si did indeed nucleate and grow using crystal defects introduced by cryogenic pre-deformation as heterogeneous nucleation sites.
[0041] Further quantitative statistical analysis of the precipitated phases showed that the number density of δ-Ni2Si precipitates in the alloy obtained in Example 1 was as high as 74.63 μm. -2 .Depend on Figure 3 It can be seen that, in terms of size distribution, the proportion of δ-Ni₂Si precipitates with a size smaller than 20 nm is 39.22%, the proportion of δ-Ni₂Si precipitates with a size of 20-30 nm is 53.59%, and the proportion of δ-Ni₂Si precipitates with a size of 30-40 nm is 7.19%. The average ECD (equivalent circle diameter) is 21.76 nm, and the average Feret size is 28.92 nm. A systematic comparison of the precipitation characteristics of Comparative Example 1 (conventional room temperature rolling + aging) with the data of this invention further reveals the essential control of cryogenic pre-deformation. The number density of precipitates in Comparative Example 1 is only 14.21 μm. -2 Less than one-fifth of the size of the precipitate in the present invention; in its size distribution, the proportion of precipitates in the 20-50 nm range is as high as 68.11% ( Figure 3 The average ECD is 22.15 nm, and the average Feret size is 30.11 nm. In comparison, this invention significantly increases the number density while reducing the average ECD from 22.15 nm to 21.76 nm and the average Feret size from 30.11 nm to 28.92 nm, achieving a unique precipitation combination of "explosive increase in number density and slight refinement of average size." This combination profoundly reflects the essential advantage of this invention in precipitation kinetics: the high-density uniform defects introduced by cryogenic pre-deformation provide an extremely large number of nucleation sites. During aging, the precipitation reaction proceeds in a nucleation-dominated mode—a large number of solute atoms simultaneously and independently nucleate at numerous nucleation sites, causing a sharp increase in the number of precipitated phases; simultaneously, due to the extremely small spacing between nucleation sites, the diffusion fields of solute atoms around each precipitated phase overlap early on, effectively limiting the further growth of individual precipitated phases. Therefore, with the same total amount of solute atoms, the present invention achieves a precipitation pattern of "more and finer" atoms, while the traditional process, due to the sparse nucleation sites and the local oversupply of solute, presents a precipitation pattern of "few and coarse" atoms.
[0042] A comparative analysis was performed on the EDS surface scan distribution of Ni element in Example 1 and Comparative Example 1. For example... Figure 4As shown, in the sample treated by the method of this invention, Ni element is uniformly distributed in the matrix without obvious local segregation, corresponding to a uniform distribution of the precipitated phase. In contrast, in the comparative sample, Ni element is significantly enriched in specific regions such as dislocation cell walls, corresponding to a localized aggregation of the precipitated phase. This difference in elemental distribution further confirms the significant effect of this invention in improving the uniformity of the precipitated phase distribution from a chemical composition perspective.
[0043] (2) Comprehensive performance test results and analysis The mechanical properties and electrical conductivity of the alloys obtained in Example 1 and Comparative Example 1 were tested. Regarding strength, the tensile strength of the alloy obtained in Example 1 was 716.42 MPa, while that of Comparative Example 1 was 689.09 MPa. The method of this invention improved the tensile strength by approximately 4.0%. This improvement is mainly attributed to the significant increase in the number density of precipitates. According to precipitation strengthening theory, the hindering effect of precipitates on dislocation movement is directly related to their number density. When dislocations encounter dispersed precipitate particles during their movement, they need to cut through or bypass these particles to continue sliding. The greater the number of precipitate particles per unit volume, the more frequent and significant the hindering effect on dislocation movement. In the method of this invention, the number density reaches as high as 74.63 μm. -2 The number density of precipitated phases is higher than that of 14.21 μm in traditional room temperature processes. -2 The tensile strength of the alloy is increased by approximately 60.42%, which means that the number of strengthening particles that hinder dislocations per unit volume in the alloy of this invention is 5.25 times that of the conventional process. The obstacles that dislocation movement needs to overcome are greatly increased, thereby significantly improving the tensile strength of the alloy.
[0044] In terms of plasticity, the alloy obtained in Example 1 achieved an elongation of 12.71%, while Comparative Example 1 only achieved 7.53%, representing an improvement of 68.8%. This significant improvement in plasticity is not due to a simple compromise between strength and plasticity, but rather to a fundamental improvement in the uniformity of precipitate distribution. In traditional processes, precipitates are locally enriched at dislocation cell walls, leading to significant strength differences within the alloy's micro-regions. During tensile deformation, the sparsely precipitated soft regions preferentially undergo plastic deformation, while the precipitated-rich hard regions restrict deformation propagation. This uneven deformation inevitably leads to localized stress concentration and premature fracture, thus limiting the overall elongation. This invention achieves a uniform distribution of precipitates in the matrix, making the strength of each region more consistent. During deformation, uniform and coordinated plastic flow can occur through dislocation slip, thereby delaying necking and fracture, and significantly improving elongation.
[0045] Regarding conductivity, the alloy obtained in Example 1 exhibits a conductivity of 48.70% IACS, compared to 47.52% IACS in Comparative Example 1, representing an improvement of approximately 2.5%. This increase in conductivity stems from the thoroughness of the precipitation reaction. Because this invention provides a high density of uniform nucleation sites, Ni and Si solute atoms are more fully precipitated from the matrix during aging, significantly reducing the concentration of residual solute atoms. This reduction in solute atoms directly weakens their distortion effect on the matrix lattice, thereby reducing the scattering of conductive electrons and improving conductivity.
[0046] Further analysis was conducted on the variation of conductivity with aging time. Figure 5 The curves show that as the aging time increases from 2 hours to 4 hours, the conductivity of the products obtained by both the method of this invention and the conventional process gradually increases, with the conductivity of the method of this invention consistently higher than that of the conventional process. When the aging time is extended to the range of 4-5 hours, the conductivity of the product obtained by the method of this invention shows a gradual decreasing trend, while the conductivity of the conventional room temperature process continues to increase slowly, but its conductivity value at 5 hours is still lower than the peak value reached by the method of this invention at 4 hours. This variation pattern has important physical implications: the method of this invention, due to sufficient nucleation sites and a low nucleation energy barrier, completes most of the precipitation reaction within a relatively short aging time (3-4 hours), reaching the peak conductivity. In contrast, the conventional process, due to limited and unevenly distributed nucleation sites, proceeds with a slower precipitation reaction; its conductivity can still slowly increase at 4-5 hours, but its kinetic lag prevents its peak value from surpassing that of the method of this invention. The decrease in conductivity of the method of the present invention after more than 4 hours may be due to the coarsening of the precipitated phase or changes in the interface structure with the matrix during the over-aging stage, which increases the scattering of electrons. However, this does not affect the overall performance advantages obtained by the present invention within the optimized aging regime.
[0047] In summary, this invention introduces high-density, uniformly distributed crystal defects through cryogenic pre-deformation, effectively controlling the nucleation and growth behavior of the δ-Ni2Si precipitates and achieving comprehensive optimization of the precipitate number density, size distribution, and spatial distribution. The resulting improvement in microstructure leads to a simultaneous increase in the alloy's strength, plasticity, and electrical conductivity, effectively solving the technical challenge of uncoordinated overall performance caused by uneven precipitation in traditional processes.
[0048] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the invention in any way. All equivalent transformations or modifications made in accordance with the essence of the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for controlling the distribution of precipitated phases in Cu-Ni-Si alloys, characterized in that, This includes the following steps: Step (1): Using the solution-treated Cu-Ni-Si alloy as raw material, the raw material is subjected to cryogenic pre-deformation treatment. The cryogenic pre-deformation is carried out in the liquid nitrogen temperature range, with a total deformation of 65% to 85%, completed in 5 to 8 passes. After each pass of rolling, the alloy is immersed in liquid nitrogen and held for 10 to 30 minutes. Cryogenic pre-deformation can introduce crystal defects into the raw material. The crystal defects include planar slip dislocation arrays, stacking faults, and nanotwins. Step (2): The Cu-Ni-Si alloy after cryogenic pre-deformation is subjected to aging treatment at a temperature of 400-450°C and a holding time of 2-4 hours, so that the δ-Ni2Si precipitate can nucleate and grow using the crystal defects as heterogeneous nucleation points, thereby controlling the distribution of the δ-Ni2Si precipitate in the Cu-Ni-Si alloy.
2. The method according to claim 1, characterized in that, The cryogenic pre-deformation is cryogenic rolling.
3. The method according to claim 1, characterized in that: In the Cu-Ni-Si alloy obtained in step (2), the number density of the δ-Ni2Si precipitate phase is 74.63 μm. -2 .
4. The method according to claim 3, characterized in that: In the Cu-Ni-Si alloy obtained in step (2), the proportion of δ-Ni2Si precipitates with a size of less than 20 nm is 39.22%, the proportion of δ-Ni2Si precipitates with a size of 20-30 nm is 53.59%, and the proportion of δ-Ni2Si precipitates with a size of 30-40 nm is 7.19%.
5. The method according to claim 3, characterized in that: The δ-Ni2Si precipitates are spherical or ellipsoidal and are distributed in the alloy matrix and at the crystal defects.
6. The method according to claim 3, characterized in that: Repeating steps (1) and (2) once can increase the number density of the δ-Ni2Si precipitate.
7. The method according to claim 1, characterized in that: The Cu-Ni-Si alloy obtained in step (2) has a conductivity of 48.70% IACS, a tensile strength of 716.42 MPa, and an elongation of 12.71%.